Integrating Human Rights and Biosecurity in International Law: Toward a Holistic Framework - Noor Dzuhaidah Osman; Syahirah Abdul Shukor; Fareed Mohd Hassan; Nurfarhah Farhanim Shafie (Badan Penelitian dan Pengembangan Hukum dan HAM, 2026)
Non-Indexed Publication